2021
DOI: 10.3390/ijerph182010868
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Character Strengths and Subjective Wellbeing: Evidence from Greece under Lockdown during COVID-19 Pandemic

Abstract: COVID-19 was first identified in December 2019. As long as this type of coronavirus was new, the main way for governments to avoid the spread of the infection was enforced quarantine. Besides public health protection, quarantine can have a psychological impact on the residents, with main symptoms being angst, anxiety, depressive, and PTSD symptoms. As it has been found that character strengths can promote subjective wellbeing, the purpose of the study was to examine this relationship under the new situation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
(188 reference statements)
0
8
0
Order By: Relevance
“…These findings were also in line with evidence from pre-pandemic studies [ 34 ]. A balanced social environment and resilience of character are essential for preserving the mental well-being during the home-confinement periods [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also in line with evidence from pre-pandemic studies [ 34 ]. A balanced social environment and resilience of character are essential for preserving the mental well-being during the home-confinement periods [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the conceptualization of character strengths differs from the traditional personalities, that they are malleable by targeted training or after traumatic life events [ 11 ] and easier to change. On the other hand, as an emerging body of work has demonstrated the protective role of character strengths as a coping mechanism to buffer between the negative impacts of the pandemic and mental health [ 23 , 26 , 27 , 29 , 35 ], the observed changes in character strengths in our study might be temporary and reflect more of a situational reaction to hard times. In addition, despite suffering the negative impacts like health threats, stress and depress [ 3 ], exposure to traumatic events like the pandemic could also associate with positive outcomes [ 61 ].…”
Section: Discussionmentioning
confidence: 74%
“…Casali et al [ 28 ] converged the 24 character strengths into one factor and the results from a longitudinal study ( n = 254) showed character strengths had a direct effect on mental health during the second wave of the pandemic by comparing the first and the second wave of the pandemic in Italy. A study of people from Greece ( n = 354) also proved most of the 24 human strengths were “able to act” to maintain or enhance subjective well-being, especially love, curiosity, persistence, hope, and zest with a strong association with subjective well-being under quarantine [ 29 ]. Coincidentally, the longitudinal study [ 30 ] conducted for Spain ( n = 348) grouped the character strengths into five factors (i.e., fortitude, goodness, intellectual, interpersonal, and restraint) and discovered that all the factors positively correlated with life satisfaction and positive affect over a one-month period during the COVID-19 pandemic lockdown.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations